Feminizing genitoplasty in childhood: aiming for achievable outcomes - Amr Abdelhamid AbouZeid (SpringerOpen, 2020)
Abstract Background Early genital reconstruction may be recommended in cases of congenital adrenal hyperplasia to avoid the stigma that can affect these individuals with variable degrees through different cultures. However, the separation and mobilization of a high vagina has remained challenging with less satisfactory surgical outcomes. Therefore, the value of early vaginal reconstruction has been questioned in favour of delaying the whole repair after puberty. In this report, the author has adopted the third option in-between, which comprises early reconstruction of the external genitalia and delaying the more challenging vaginal reconstruction (if needed) to be performed after puberty. Results The study included ten consecutive cases of CAH who underwent feminizing genitoplasty during the period 2016 through 2019. Their age at operation ranged from 8 to 84 months (mean 31; median 15). In five cases (50%), the technique of limited urogenital sinus mobilization adopted in this report succeeded in bringing the vaginal introitus down to the perineum. Those cases had originally a low vagina. In the rest of cases, labial retraction showed a common but wide urogenital introitus perfectly lined by urogenital mucosa. The outcomes have been considered satisfactory to a great extent for both parents and doctors regarding cosmesis and lack of functional complications (voiding problems). Longer follow up is still needed to assess the sexual function when these girls become sexually active. Conclusion In cases of congenital adrenal hyperplasia, reduction clitoroplasty combined with partial urogenital sinus mobilization can achieve predictable and satisfactory outcomes. In about 50% of cases, this approach is sufficient to bring the vagina down to the perineum. In the other half of cases with higher vagina, the possibility of satisfactory sinus intercourse can be studied when these girls grow and become sexually active; otherwise, a delayed vaginal reconstruction may turn to be necessary.